Peran Komunikasi dalam Pengembangan Kelembagaan Ketahanan Pangan Masyarakat ; Kasus Lumbung Pangan di Ciamis, Jawa Barat - N. Koesoemowardani; Sumardjo . (Institut Pertanian Bogor, 2008)
The rice barn have important role in the farmer food security, especially at period of shortage before harvest.Nevertheless, a lot of the rice barn have still social function. To supported the community food security, the role ofrice barn must be changed to economics oriented. The objective of this research are (1) to study some factors thatinfluence communication models, (2) to study correlations of communication models and supporting factors tobehavior change at members and board of rice barn, and (3) correalations of behavior change to accelaration ofrice barn. This research was conduct in three sub-district on Ciamis District, West Java. The result indicated thatindividual characteristic and external variables were significant related to communication models. The supportingvariables and communication models were significant related to the behavior change of the member and board of therice barn. The better of trust, transparancy and participation in the rice barn management were related to theaccelerated function of the rice barn food security.